Debris‐flow release processes investigated through the analysis of multi‐temporal LiDAR datasets in north‐western Iceland. Issue 1 (20th September 2018) - Morino, Costanza; Conway, Susan J.; Balme, Matthew R.; Hillier, John; Jordan, Colm; Sæmundsson, Þorsteinn; Argles, Tom
Abstract: Debris flows are fast‐moving gravity flows of poorly sorted rock and soil, mixed and saturated with water. Debris‐flow initiation has been studied using empirical and experimental modelling, but the geomorphic changes, indicative of different triggering processes, are difficult to constrain with field observations only. We identify signatures to distinguish two different debris‐flow release styles by integrating high‐resolution multi‐temporal remote sensing datasets and morphometric analysis. We analyse debris flows sourced above the town of Ísafjörður (Iceland). Two debris‐flow triggering processes were previously hypothesised for this site: (i) slope failure, characterised by landslides evolving into debris flows; and (ii) the fire‐hose effect, in which debris accumulated in pre‐existing, steep‐sided bedrock passages is transported by a surge of water. It is unknown which process dominates and determines the local risk. To investigate this question, we compare airborne LiDAR elevation models and aerial photographs collected in 2007 with similar data from 2013. We find that two new debris‐flow tracks were created by slope failures. These are characterised by steep sliding surfaces and lateral leveed channels. Slope failure also occurred in two large, recently active tracks, creating the preparatory conditions for the fire‐hose effect to mobilise existing debris. These tracks show alternating zones of fill and scour along their length, and debris stored below the source‐area at rest angles >35°. Our approach allows us to identify and quantify the morphological changes produced by slope failure release process, which generated the preparatory conditions for the fire‐hose effect. As debris flows are rarely observed in action and morphological changes induced by them are difficult to detect and monitor, the same approach could be applied to other landscapes to understand debris‐flow initiation in the absence of other monitoring information, and can improve the identification of zones at risk in inhabited areas near hillslopes with potential for debris flows. © 2018 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : We compare two airborne datasets (LiDAR topography and aerial images) to study debris flows in Ísafjörður (Iceland). We assess and distinguish the role of two release mechanisms in debris‐flow generation: slope failure and fire‐hose effect. We find that slope failure is the dominant debris‐flow release process on the slope of Ísafjörður. Two new debris‐flow tracks were created by slope failures, which also created the preparatory conditions for the fire‐hose effect to mobilise existing debris in two other recently active tracks.